2020
DOI: 10.1128/aac.00311-20
|View full text |Cite
|
Sign up to set email alerts
|

A Choline-Recognizing Monomeric Lysin, ClyJ-3m, Shows Elevated Activity against Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a leading pathogen for bacterial pneumonia, which could be treated with bacteriophage lysins harboring a conserved choline binding module (CBM). Such kind of lysins regularly function as choline-recognizing dimers. Previously, we reported a pneumococci-specific lysin ClyJ comprising the binding domain from the putative endolysin gp20 from the Streptococcus phage SPSL1 and the CHAP (cysteine, histidine-dependent amidohydrolase/peptidase) catalytic domain from the PlyC lysin. And a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…Besides, the lysis proceeded somewhat faster at 30 • C but no statistically significant differences were found in the killing capacity after 60 min incubation in a given buffer (Figure 7C). As a whole, our results showed that optimal antipneumococcal activity of Skl compares well with those of Pal and LytA under equivalent conditions, and with those of ClyJ-3 and ClyJ-3m, two variants of a chimera built by fusing the CHAP domain of PlyC and the choline-specific CBD of the gp20 endolysin from the Streptococcus phage SPSL1 (Luo et al, 2020;Yang et al, 2020). Interestingly, the Y264H substitution reduced the bactericidal activity of Skl by several orders of magnitude (Figure 7A), further supporting the relevance of dimerization for the activity.…”
Section: Biochemical Characterization Of Skl Antipneumococcal Activitysupporting
confidence: 56%
See 1 more Smart Citation
“…Besides, the lysis proceeded somewhat faster at 30 • C but no statistically significant differences were found in the killing capacity after 60 min incubation in a given buffer (Figure 7C). As a whole, our results showed that optimal antipneumococcal activity of Skl compares well with those of Pal and LytA under equivalent conditions, and with those of ClyJ-3 and ClyJ-3m, two variants of a chimera built by fusing the CHAP domain of PlyC and the choline-specific CBD of the gp20 endolysin from the Streptococcus phage SPSL1 (Luo et al, 2020;Yang et al, 2020). Interestingly, the Y264H substitution reduced the bactericidal activity of Skl by several orders of magnitude (Figure 7A), further supporting the relevance of dimerization for the activity.…”
Section: Biochemical Characterization Of Skl Antipneumococcal Activitysupporting
confidence: 56%
“…Interestingly, the Y264H substitution reduced the bactericidal activity of Skl by several orders of magnitude (Figure 7A), further supporting the relevance of dimerization for the activity. Curiously, the antipneumococcal activity of ClyJ-3 was improved by deletion of the C-terminal tail of the CBD in the ClyJ-3m monomeric variant, which might denote a less favorable interaction of the highly active PlyC domain with the cleavable peptidoglycan bonds upon dimerization of this fully engineered lysin (Luo et al, 2020).…”
Section: Biochemical Characterization Of Skl Antipneumococcal Activitymentioning
confidence: 99%
“…Similar to ClyJ, ClyJ-3 forms a dimer conformation upon binding with a choline molecule, while ClyJ-3m forms a monomer upon choline binding. The bactericidal activity was greatly enhanced in ClyJ-3m when compared to the parental enzymes ClyJ-3 and ClyJ ( Luo et al, 2020 ).…”
Section: Enzymatically Active Domain and Cell Wall-binding Domain Of ...mentioning
confidence: 93%
“…ClyJ exhibited stronger activity against S. pneumoniae than Cpl-1, and it produced no resistance in bacteria after prolonged exposure to the enzyme ( Yang et al, 2019 ). ClyJ also has several derivatives denoted as ClyJ-3 and ClyJ-3m, which are essentially truncated versions of ClyJ ( Luo et al, 2020 ). ClyJ-3 has a shorter linker than the parental ClyJ, whereas ClyJ-3m is a variant of ClyJ-3, which has a truncated C-terminal tail.…”
Section: Enzymatically Active Domain and Cell Wall-binding Domain Of ...mentioning
confidence: 99%
“…With the aim of improving its activity, chimeric lysin ClyJ was modified by shortening its linker, which led to increased lytic activity in vivo (20-fold) and reduced cytotoxicity [ 67 ]. Remarkably, a variant of this protein, ClyJ-3m, which remains a monomer after binding choline, exhibited even higher bactericidal activity and improved the pharmacokinetic properties, such as a lesser clearance by the immune system [ 68 ]. Additionally, two new streptococcal endolysins (23TH_48 and SA01_53) have been recently identified in the oral microbiome.…”
Section: Phage Therapymentioning
confidence: 99%